2013
DOI: 10.1038/nature11900
|View full text |Cite
|
Sign up to set email alerts
|

The sarcolipin-bound calcium pump stabilizes calcium sites exposed to the cytoplasm

Abstract: The contraction and relaxation of muscle cells is controlled by the successive rise and fall of cytosolic Ca(2+), initiated by the release of Ca(2+) from the sarcoplasmic reticulum and terminated by re-sequestration of Ca(2+) into the sarcoplasmic reticulum as the main mechanism of Ca(2+) removal. Re-sequestration requires active transport and is catalysed by the sarcoplasmic reticulum Ca(2+)-ATPase (SERCA), which has a key role in defining the contractile properties of skeletal and heart muscle tissue. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
239
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(252 citation statements)
references
References 48 publications
12
239
1
Order By: Relevance
“…For instance, the P2A sarco(endo)plasmic reticulum Ca 2ϩ -ATPase (SERCA) is inhibited by the accessory proteins phospholamban and sarcolipin, small membrane proteins with a single transmembrane segment (4). Sarcolipin uncouples the SERCA pump (5) by trapping it in the Ca 2ϩ -binding conformation (6,7). Autoinhibition by a regulatory domain is observed in a closely related family of P-type ATPases, the P2B calmodulin-activated Ca 2ϩ -ATPases, which occur in both plants and animals (8 -10).…”
mentioning
confidence: 99%
“…For instance, the P2A sarco(endo)plasmic reticulum Ca 2ϩ -ATPase (SERCA) is inhibited by the accessory proteins phospholamban and sarcolipin, small membrane proteins with a single transmembrane segment (4). Sarcolipin uncouples the SERCA pump (5) by trapping it in the Ca 2ϩ -binding conformation (6,7). Autoinhibition by a regulatory domain is observed in a closely related family of P-type ATPases, the P2B calmodulin-activated Ca 2ϩ -ATPases, which occur in both plants and animals (8 -10).…”
mentioning
confidence: 99%
“…There is a high degree of sequence homology in the transmembrane regions of PLN and SLN, suggesting a similar mode of interaction with SERCA (6,7). Although studies have demonstrated that PLN and SLN use distinct structural elements and mechanisms to regulate SERCA (8,9), crystal structures of the SERCA-SLN (10,11) and SERCA-PLN (12) complexes are remarkably similar to one another.…”
mentioning
confidence: 85%
“…In the structure of the SERCA-SLN complex (10,11), Tyr 29 of SLN is proximal to Phe 88 on M2 of SERCA, although Arg 27 and Tyr 31 face away from SERCA. These latter two residues are positioned to protrude into the membrane at the hydrocarbon core-water interface, thereby acting as ballast to properly position SLN in the inhibitory complex (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this notion, mutations of an electronegative patch of a CopZ chaperone abolished Cu þ transport in AfCopA (24), which suggests that positively charged amino acids on the MB' helix are the target for chaperone interactions with the surface of the protein core. In the docked position, the chaperone Cu þ -binding site presumably is located close to the putative initial Cu þ receivers Met148, Glu205, and Asp337 (residue numbers refer to LpCopA throughout), as observed for Ca 2þ in the related Ca 2þ -transporting P-type ATPase SERCA1a (9,25). In SERCA1a, the ions are then transferred to two internal Ca 2þ -binding sites (26,27); however, the exact number, location, and chemical nature of the entry pathways in CopA proteins are unknown because the available structural information is limited to E2 states (9,10), where copper already has been deposited on the noncytosolic side.…”
Section: Additionally Intermediate States Other Than the Cornerstomentioning
confidence: 98%